MEDIA SARANA PROMOSI MAKANAN KHAS BENGKULU BERBASIS WEBSITE MENGGUNAKAN SCRIPT PHP - Kanedi, Indra; Yupianti, Yupianti; Utami, Feri Hari (Jurnal Media Infotama, 2013)
Web Tekonologi also keeping pace with the development of internet technology . The development of web technology from the first era of the web (Web 1.0) , where visitors can only find ( searching ) and look ( browsing ) data information available on the web, then rub in the second era of web development ( Web 2.0 ), where visitors can do interactions such as exchange of information , the exploitation of information , and online community building . The development of web technology required to support the activities of the society that is increasingly dependent on the internet. Was their main purpose and do research is to make a Media Campaign Dishes Bengkulu Based Website Using PHP Script. With the Media Campaign Dishes Bengkulu Based Website Using PHP Scripts , raised allows simple dynamic website updated at any time. In addition , this website can be one of the means for the community to socialize every bengkulu of information and for some idea of how much food and a special cake was in town Bengkulu . The making of this website can be a cheaper alternative media in the promotion of special food in Bengkulu